Digitaliserad uppföljning av produktion - Evaldsson, Andreas; West, Joakim (My University, 2020)
This report is centered around the eventual need of an automated follow up system at a specific production line of a medium sized company. Whenever a fault occurs, it is manually reported on a paper. This is used for book keeping of various KPI’s (Key Performance Indicators) of the line. Specifically, the company is interested in measuring and calculating OEE, FPY, and Productivity. Reliable and accurate data is mandatory to obtain a representative KPI. Thus, the manual "low tech" approach to data collection puts a lot of pressure on the responsible operators. The company is currently in a phase of development to keep up with international standards of automated industry. That is their motivation to investigate the possibility and need for a digitalized and automated follow up system. Areas of improvment concerning work procedures were also analyzed. To draw any conclusions, however, the theory about KPI’s, TPM (Total Productivity Management) and Lean Production had to be understood. This was done by reading books, scientific articles and reports about the subjects. Interviews and consultations with employees were also conducted to reassure a good understanding of the entire work procedure. The document in which KPI’s, failures and stop reasons was altered to improve reproducibility and repeatability. This was done by implementing various filters, allowing the user to specifically target product groups and individual stations on the product line. The list containing various failures and stop reasons was also shortened to improve the efficiency and perspicuousness of the document. In the end, different follow up systems were analyzed and compared to the given specification of requirements. The choice of pursuing one or the other is in the hands of the company.
Keywords: TPM, FPY, OEE, Productivity, lean production